Chemistry Learning via Distance Learning during the Covid-19 Pandemic - Sari, Indah; Sinaga, Parlindungan; Hernani, Hernani; Solfarina, Solfarina (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research is a descriptive study that describes the learning of chemistry during the Covid-19 pandemic. The respondents in this study were 127 high school students from the West Java and Banten provinces. A Google Form questionnaire was used to collect the data. The results showed that the most widely used online class applications were WhatsApp Group feature, Google Classroom, and Zoom. Students also used printed textbooks, e-books, and student worksheets as learning media. Students did laboratory practice at home using easily found tools and materials. However, a small portion of the respondents (< 11 %) used materials purchased from a chemical store, and another small portion of the respondents (< 14 %) used virtual laboratories. They reported the results of their practice by making a laboratory practice report as well as through video activities and Microsoft PowerPoint for presentation. Students learn from home with varying durations. Most students experienced obstacles during the learning process so that they prefer learning face-to-face in class as usual. Therefore, the teacher must prepare a variety of strategies for distance learning so that the students can learn chemistry from home with fun. Some strategies that can be applied are providing audio-visual learning media or computer/android-based games for chemistry, using the online class application that accommodates interactions similar to face-to-face learning, providing laboratory practice using tools and materials that can be easily found around the house, providing virtual lab application, and providing more opportunities for students to ask questions about chemistry topics that they do not understand.